2017
DOI: 10.1080/21645515.2017.1302046
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus and its association with Fascin expression in colorectal cancers in the Syrian population: A tissue microarray study

Abstract: Colorectal cancer (CRC) is the third most common malignancy in both men and women worldwide. Colorectal carcinogenesis is a complex, multistep process involving environmental and lifestyle features as well as sequential genetic changes in addition to bacterial and viral infections. Viral infection has a proven role in the incidence of approximately 20% of human cancers including gastric malignancies. Accordingly, Epstein-Barr virus (EBV) has been recently shown to be present in human gastric cancers, which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
(60 reference statements)
1
25
0
Order By: Relevance
“…The highest reported EBV-positivity in CRC was up to 46%, with the majority of the studies reporting EBV positivity of 20–40% [ 19 , 28 , 41 , 42 ]. Our study indicated the individual presence of EBNA1 and LMP1 genes of EBV in 14% and 25% of the samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest reported EBV-positivity in CRC was up to 46%, with the majority of the studies reporting EBV positivity of 20–40% [ 19 , 28 , 41 , 42 ]. Our study indicated the individual presence of EBNA1 and LMP1 genes of EBV in 14% and 25% of the samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The combined oncogenic effects of viral infections have been recognized as potential oncogenic drivers in various cancers [ 6 ]. Oncoviruses can lead to the onset and progression of cancer via commonly shared pathways including WNT/β-catenin, JAK/STAT/SRC, PI3k/Akt/mTOR, and/or RAS/MEK/ERK signaling pathways [ 6 , 8 , 14 , 41 ]. A study conducted by Guidry and Scott [ 63 ] showed that co-infection by HPV and EBV enhances EBV persistence either via latency or increased viral replication or by aggregating HPV oncogene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Since EBV assessment by IHC is not routinely employed in CRC and other colorectal malignancies, the thresholds for positivity varied across the studies (1-10%) while several studies did not report the threshold for positivity. 20,25,27,30 We point out here the importance of the method of EBV detection as it may play a key role in elucidating not only the presence but also the potential contribution of EBV to colorectal carcinogenesis. Most studies used PCR and/or IHC for EBV detection.…”
Section: Discussionmentioning
confidence: 99%
“…Most positive studies revealed EBV positivity rate to bẽ 20-40% of the cases. 20,23,26,29,30,32,34 A study of Salyakina et al 26 reported a common co-infection of EBV with other viruses in 20% of the CRC samples (Cytomegalovirus and Human Herpesvirus 6B/HHV-6B/). An interesting case study by Chang et al 28 on collision colorectal tumors (adenocarcinoma and non-Hodgkin lymphoma) revealed serum EBV positivity.…”
Section: Status Of Ebv In Colorectal Cancermentioning
confidence: 99%
“…In a study of 90 CRC specimens, EBV proteins were detected in nearly a third of the tissues, compared to a detection rate of only 4% in adjacent non-cancerous control specimens [26]. Another study used PCR and tissue microarray (TMA) analysis to show that EBV was present in 36% of 102 CRC tissue samples, and EBV was also associated with a more aggressive type of CRC [27]. Recent research suggests that a coinfection of EBV and HPV may play an important role in the progression of cervical cancer [28].…”
Section: Oncoviruses and Breast Cancermentioning
confidence: 99%